Core J2EE™ Patterns: Best Practices and Design Strategies, Second Edition - Alur, Deepak; Crupi, John; Malks, Dan (Core design series., 2003)
"The Java landscape is littered with libraries, tools, and specifications. What's been lacking is the expertise to fuse them into solutions to real-world problems. These patterns are the intellectual mortar for J2EE software construction." --John Vlissides, co-author of Design Patterns, the "Gang of Four" book "The authors of Core J2EE Patterns have harvested a really useful set of patterns. They show how to apply these patterns and how to refactor your system to take advantage of them. It's just like having a team of experts sitting at your side." --Grady Booch, Chief Scientist, Rational Software Corporation "The authors do a great job describing useful patterns for application architectures. The section on refactoring is worth the price of the entire book!" --Craig McClanahan, Struts Lead Architect and Specification Lead for JavaServer Faces "Core J2EE Patterns is the gospel that should accompany every J2EE application server...Built upon the in-the-trenches expertise of its veteran architect authors, this volume unites the platform's many technologies and APIs in a way that application architects can use, and provides insightful answers to the whys, whens, and hows of the J2EE platform." --Sean Neville, JRun Enterprise Architect, Macromedia Developers often confuse learning the technology with learning to design with the technology. In this book, senior architects from the Sun Java Center share their cumulative design experience on Java 2 Platform, Enterprise Edition (J2EE) technology. The primary focus of the book is on patterns, best practices, design strategies, and proven solutions using the key J2EE technologies including JavaServer Pages(TM) (JSP(TM)), Servlets, Enterprise JavaBeans(TM) (EJB(TM)), and Java(TM) Message Service (JMS) APIs. The J2EE Pattern Catalog with 21 patterns and numerous strategies is presented to document and promote best practices for these technologies. Core J2EE Patterns, Second Edition offers the following: J2EE Pattern Catalog with 21 patterns--fully revised and newly documented patterns providing proven solutions for enterprise applications Design strategies for the presentation tier, business tier, and integration tier Coverage of servlets, JSP, EJB, JMS, and Web Services J2EE technology bad practices Refactorings to improve existing designs using patterns Fully illustrated with UML diagrams Extensive sample code for patterns, strategies, and refactorings.